Age at menopause in Latin America (2006)
Objective: To assess the age at menopause (AM) in Latin America urban areas. Design: A total of 17,150 healthy women, aged 40 to 59 years, accompanying patients to healthcare centers in 47 cities of 15 Latin American countries, were surveyed regarding their age, educational level, healthcare coverage, history of gynecological surgery, smoking habit, presence of menses, and the use of contraception or hormone therapy at menopause. The AM was calculated using logit analysis. Results: The mean age of the entire sample was 49.4 ± 5.5 years. Mean educational level was 9.9 ± 4.5 years, and the use of hormone therapy and oral contraception was 22.1% and 7.9%, respectively. The median AM of women in all centers was 48.6 years, ranging from 43.8 years in Asuncion (Paraguay) to 53 years in Cartagena de Indias (Colombia). Logistic regression analysis determined that women aged 49 living in cities at 2,000 meters or more above sea level (OR = 2.0, 95% CI: 1.4-2.9, P < 0.001) and those with lower educational level (OR = 1.9, 95% CI: 1.3-2.8, P < 0.001) or living in countries with low gross national product (OR = 2.1, 95% CI: 1.5-2.9, P < 0.001) were more prone to an earlier onset of menopause. Conclusions: The AM varies widely in Latin America. Lower income and related poverty conditions influence the onset of menopause.